“¿Cuál es el impacto de la corrupción en el crecimiento económico de los Países Andinos? Evidencia para el período 1996 – 2019” - Mendieta Lamar, John Ramiro (2021)
In recent years, corruption in Latin America has become a problem of general interest, each year the cost of corruption is equivalent to approximately 5% of world product, equivalent to 2.5 trillion dollars. In general, 24% of Latin Americans trust that the elections are honest, 15% think that corruption is not present in the government, while 35% have full confidence in justice and 30% trust the government . Therefore, the objective of this research is; determine the effect of corruption on the economic growth of the Andean countries in the period 1996-2019. Data from the World Bank (WB, 2020) and World Indicators of Good Governance (IMBG, 2020) were used in which the Hausman test (1978), the Wooldridge test (2002) and the Wald test (1993) will be applied. Once the model has been corrected, a basic generalized least squares (GLS) regression will be carried out, finally the causality test proposed by Dumitrescu and Hurlin (2012) was applied. The results of the GLS determine that there is a negative relationship between corruption and economic growth and a high significance with its control variables. The causality test determined the existence of two-way causality between corruption and economic growth. Finally, it is suggested that the creators of policies and laws are aware of the effects of the different factors that corruption generates in order to have the ability to provide alternative solutions.